Investigation of anticancer peptides from zophobas moria fabricus - Chowdhury, Silvia; Yusof, Faridah; Faruck, Mohammad Omer; Sulaiman, Nadzril (2015)
Cancer is an extremely complicated disease and still presents enormous challenges, in the medical world. Drug-based chemotherapy treatment are usually applied especially to combat cancer that cannot be treated by any other cancer treating method. Up-to-date there are so many drugs been researched and discovered and some of them are at the different phases of trials before commercialization. Anticancer agents based on natural resources are preferred compared to chemical based because the later can also be harmful towards healthy cells, thus elevating the side effects of chemotherapy. In this study, anticancer peptides has been recovered from non-immunized final instar larvae of Zophobas morio Fabricus using acidified (triflouroacetic acid) solvent (ethanol and isopropanol). Results showed that the two different extracts inhibits growth of MCF-7 breast cancer cell line at varying degrees. The results of cytotoxicity investigation and fluorescence microscopic observations conclude that the extracts could significantly inhibit MCF-7 cell viability and disrupt their cell morphology. Statistical analysis showed ethanolic and isopropanolic extract have IC50 of 1.7 mg/ml and 0.7 mg/ml respectively. This work may present the first initiative towards recovering anticancer peptides from natural, low cost, easily found insect larvae, whereby it can be potentially developed as peptide-based drug to be used in chemotherapy. Future work includes purifying, identification and characterization of peptides.